Dynamic behavior of a floating water droplet with hydrocarbon-degrading bacteria - Asadi, F.; Phan, Chi; Obanijesu, E. (Elsevier Ltd, 2015)
This study investigated the influence of hydrocarbon-degrading bacteria on the floating water droplet, which aims to explore a safer removal method for oil spills. An aqueous solution was prepared by mixing a bacterial mixture, SDS and NaCl, and then deposited on the surface of paraffin oil. The floatable volume of bacteria-containing droplet was smaller than the previously reported droplet, which was stabilized by surfactant only. Nevertheless, the water droplet remained floating effectively for the bio-processes. The bacterial activities have distinguished influence on the floating behavior. First, the bio-film was formed on the air/water interface, and noticeably reduced the evaporation rate. Second, the water was removed in ∼30 min. The results provide important new insights for removing oil spills by an economical and environmentally friendly method. The method can be combined with the current practices to reduce the ecological impact of the oil spills.